Alpha-linolenic acid protects against cardiac injury and remodelling induced by beta-adrenergic overstimulation1. Issue 7 (8th July 2015) - Folino, A.; Sprio, A. E.; Di Scipio, F.; Berta, G. N.; Rastaldo, R.
<x xml:space="preserve">Abstract</x> α-Linolenic acid (ALA)-enriched diet prevented isoproterenol (ISO)-induced fibrosis in the ventricular myocardium.